Special Nanomaterials and Surface Treatment Special topic volume with invited peer-reviewed papers only - Chen, Yi Cheng; Tsukamoto, Hideaki; Zhao, Yuyuan; Pramata, Azzah Dyah (Solid State Phenomena, 2023)
The special edition is dedicated to the recent issues in modern materials science and technologies of materials synthesis and processing and will be useful to specialists in machinery and chemical production. Steel, Composite, Coating, Surface Treatment, Finishing, Direct Laser Deposition, Electropolishing, Plasma Nitrocarburizing, Single Point Incremental Forming, Laser Welding, Mechanical Properties, Nanoparticles, Nanomaterials, Biosynthesis Materials Science, Nanoscience.